The Research of The Relationship Between The Problem Solving Skills & Metacognitive Awareness of Middle School Students and The Social Emotional Learning - YÜKSEL, MÜGE (CUKUROVA UNIV, 2021)
The aim of this study is to investigate the relationship between the problem solving skills of the 6th and 7th grade students in the middle school and the cognitive awareness with social-emotional learning. The sample of the study consisted of 295, 6th grade and 7th grade (195 girls, 100 boys) students selected using random sampling method. As a measurement tool, Problem Solving Inventory for Children, Metacognitive Awareness Inventory for Children and Social-Emotional Learning Scale Short Form were used. According to the findings of the study; It is seen that scale scores differ according to gender. Boys have more confidence in the problem-solving process than girls; girls were found to have more self-determination in problem solving processes. It is observed that girls have higher levels of social-emotional learning than boys. Another finding obtained from the study is; It was found that problem solving skills contribute to explaining social emotional learning scores, but the fact that problem-solving skills and metacognitive awareness were considered together made a significant contribution to the problem-solving skills. According to the results, supporting problem solving skills increases social emotional learning, and at the same time, high metacognitive awareness contributes positively to social emotional learning. Therefore, it is thought that supporting these skills starting from pre-school period will contribute positively to learning processes. In order to improve social emotional learning, it can be suggested that metacognitive awareness should be included in school guidance services, curricula, group guidance and counseling activities as well as problem solving skills in order to increase effectiveness.
Keywords: Metacognitive awareness; Social-emotional learning; problem solving skills; GENDER-DIFFERENCES; TEACHERS; NEED